Immune Response of Walking Catfish (Clarias macrocephalus Gunther) to Vaccination by Injection, Immersion and Oral Administration - Nontawith Areechon; Nilubol Kitancharoen; Kamonporn Tonguthai (Agriculture and Natural Resources, 1992)
Walking catfish (Clarias macrocephalus Gunther) were immunized with vaccine prepared from formalin-killed Aeromonas hydrophila by injection, immersion and oral administration. Antibody titer in the serum and disease protection upon challenge with virulent A. hydrophila were investigated. Walking catfish intraperitoneally injected with vaccine mixed with Freund’s complete adjuvant had the average serum antibody titer of 100.00 and 1105.30 for the primary and secondary immune response while walking catfish vaccinated by intraperitoneal injection with regular vaccine, hyperosmotic immersion and direct immersion had the average titer of 92.20, 444.60; 76.10, 122.60 and 33.75, 61.20 respectively. Injection induced the best protection against A. hydrophila with no mortality while direct and hyperosmotic immersion could protect 60.5 and 77.20 percent of vaccinated fish respectively. Vaccination by oral administration did not show good potency in terms of generating serum antibody titer but still produced better disease protection than unvaccinated fish.